Cleome arabica leaf extract has anticancer properties in human cancer cells. (17th July 2013) - Tigrine, Chafia; Bulzomi, Pamela; Leone, Stefano; Bouriche, Hamama; Kameli, Abdelkarim; Marino, Maria
Abstract: Context : Cleome arabica L. (Capparidaceae) is a desert plant widely distributed in the North part of Africa whose leaves are used in traditional medicine as a sedative for abdominal and rheumatic pains. Objectives: The anticancer activity of methanol Cleome arabica leaf extracts (CALE) is investigated in different human cancer cell lines. Materials and methods : Five different human cancer cell lines, representative of the most common cancers in Western countries (i.e., breast adenocarcinoma, colon carcinoma, neuroblastoma, hepatoma, cervix carcinoma) were treated with different concentrations of CALE (i.e., 1, 5, 10, 25, 50, 100 and 200 µg/ml). Cell viability and cell cycle were measured by using a hemocytometer chamber and a cytofluorimeter, respectively. Epidermal growth factor (EGF) was used as a positive control. Western blots were performed to evaluate the CALE effects on pathways involved in cell growth regulation and on apoptotic cascade activation. Results and conclusion : Our results confirm that CALE has a high content of polyphenolic compounds (i.e., 32.21 ± 3.44%), mainly as flavonoids (24.56 ± 4.67%). In all tested cell lines CALE treatment reduces cell number in a dose-dependent manner (ED50  = 175 ± 30 µg/ml). CALE (100 and 200 µg/ml) increases by three-fold the activation of the apoptotic cascade involving caspase-3 activation and the cleavage of its substrate poly(ADP-ribose) polymerase (PARP). Intriguingly, CALE treatment (200 µg/ml) also blocks EGF-induced cell growth by preventing the growth factor-triggered AKT and ERK phosphorylation. As a whole, these data strongly suggest that CALE possesses anticancer effects in all tested cancer cell lines.